2016
DOI: 10.1128/aac.03130-15
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Mechanism of Action of Lactoferrin: Identification of H + -ATPase (P 3A -Type) as a New Apoptotic-Cell Membrane Receptor

Abstract: bHuman lactoferrin (hLf) is a protein of the innate immune system which induces an apoptotic-like process in yeast. Determination of the susceptibility to lactoferrin of several yeast species under different metabolic conditions, respiratory activity, cytoplasmic ATP levels, and external medium acidification mediated by glucose assays suggested plasma membrane Pma1p (P 3A -type ATPase) as the hLf molecular target. The inhibition of plasma membrane ATPase activity by hLf and the identification of Pma1p as the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 47 publications
7
44
0
Order By: Relevance
“…A growing number of studies provide evidence that LF directly interacts with the fungal cell surface and acts on intracellular targets. Various mechanistic actions have been reported, including alteration of cell surface permeability and changes in membrane potential (38); mitochondrial dysfunction, causing intracellular reactive oxygen species accumulation (21,39); and caspase activation and cytochrome c release (18). Similarly, the LF peptides lactoferricin and lactoferrampin are known to act by binding to and disrupting the fungal cell membrane and have been observed to be rapidly internalized by cells (20,40).…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies provide evidence that LF directly interacts with the fungal cell surface and acts on intracellular targets. Various mechanistic actions have been reported, including alteration of cell surface permeability and changes in membrane potential (38); mitochondrial dysfunction, causing intracellular reactive oxygen species accumulation (21,39); and caspase activation and cytochrome c release (18). Similarly, the LF peptides lactoferricin and lactoferrampin are known to act by binding to and disrupting the fungal cell membrane and have been observed to be rapidly internalized by cells (20,40).…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae (33) and lactoferrin (>600% increase) in C. albicans (17). Both omeprazole and lactoferrin are described to be Pma1 inhibitors, although omeprazole is not fully capable of inhibiting extracellular acidification (33).…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae , it was shown that hLf induces cell death in a mitochondrial and caspase-dependent way that is characterized by caspase activation, ROS accumulation and cytochrome c release (Acosta-Zaldivar et al, 2016). Work by the same group in C. albicans indicated that the proton-translocating ATPase Pma1p, which is a primary contributor to pH regulation in yeasts, was the target of hLf, inducing lethal mitochondrial dysfunction (Andres et al, 2016). …”
Section: Structure and Antifungal Activity Of Whole Lactoferrinmentioning
confidence: 99%